Profitaility and Dividend Payout Among Construction Companies Listed at the Nairobi Securities Exchange (International Journal of Scientific Research and Management (IJSRM), 2021)
Being one of the major drivers for investing in stocks, dividend payment has been center of interest among stakeholders mainly investors, management and academic fraternity has been in attempt to investigate the causes of dividend payout. Besides the numerous studies that have been done on this subject, no amicable solution has been agreed upon regarding the influence of profitability on dividend payout with reference to listed construction firms. It is against this puzzle that this study aimed to determine the influence of the level of profit on the Dividend payout among construction companies listed at NSE. Anchored on signaling theory, the study adopted a descriptive design. A total sample population is constituted with all the five construction firms which are quoted on the Nairobi security Exchange, which constitute the sample size under the study. Secondary data was gathered by use of a secondary data collection schedule. The study performed both descriptive and inferential analyses. Results indicate that profitability (β = .971, p = .000<.05) significantly influences dividend payout. Based on the findings, the study rejects the null hypothesis that states that level of profit does not significantly influence dividend payout of construction companies listed at NSE and concludes that level of profit significantly influences dividend payout of construction companies listed at NSE. The study recommended that construction companies quoted at the Nairobi Security Exchange should aim to improve their levels of profit in order to facilitate plans of dividend payment. Being one of the major drivers for investing in stocks, dividend payment has been center of interest among stakeholders mainly investors, management and academic fraternity has been in attempt to investigate the causes of dividend payout. Besides the numerous studies that have been done on this subject, no amicable solution has been agreed upon regarding the influence of profitability on dividend payout with reference to listed construction firms. It is against this puzzle that this study aimed to determine the influence of the level of profit on the Dividend payout among construction companies listed at NSE. Anchored on signaling theory, the study adopted a descriptive design. A total sample population is constituted with all the five construction firms which are quoted on the Nairobi security Exchange, which constitute the sample size under the study. Secondary data was gathered by use of a secondary data collection schedule. The study performed both descriptive and inferential analyses. Results indicate that profitability (β = .971, p = .000<.05) significantly influences dividend payout. Based on the findings, the study rejects the null hypothesis that states that level of profit does not significantly influence dividend payout of construction companies listed at NSE and concludes that level of profit significantly influences dividend payout of construction companies listed at NSE. The study recommended that construction companies quoted at the Nairobi Security Exchange should aim to improve their levels of profit in order to facilitate plans of dividend payment.